Some New Classes of Generalized Apostol-Euler and Apostol-Genocchi Polynomials - R. Tremblay; S. Gaboury; B.-J. Fugère (International Journal of Mathematics and Mathematical Sciences)
The main object of this paper is to introduce and investigate two new classes of generalized Apostol-Euler and Apostol-Genocchi polynomials. In particular, we obtain a new addition formula for the new class of the generalized Apostol-Euler polynomials. We also give an extension and some analogues of the Srivastava-Pintér addition theorem obtained in the works by Srivastava and Pintér (2004) and R. Tremblay, S. Gaboury, B.-J. Fugère, and Tremblay et al. (2011). for both classes.